2014
DOI: 10.1136/amiajnl-2014-002901
|View full text |Cite
|
Sign up to set email alerts
|

Using the wisdom of the crowds to find critical errors in biomedical ontologies: a study of SNOMED CT

Abstract: We have demonstrated that the crowd can address the challenges of scalable ontology verification, completing not only intuitive, common-sense tasks, but also expert-level, knowledge-intensive tasks.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 18 publications
1
49
0
Order By: Relevance
“…Crowdsourcing data annotation and curation in bioinformatics can be handled well with this approach. This scheme has also been applied to provide pathway resources 68,69 , reconstruct the human metabolic network 70 , annotate molecular interactions in Mycobacterium tuberculosis 71 and identify crucial errors in ontologies 72 .…”
Section: Figurementioning
confidence: 99%
“…Crowdsourcing data annotation and curation in bioinformatics can be handled well with this approach. This scheme has also been applied to provide pathway resources 68,69 , reconstruct the human metabolic network 70 , annotate molecular interactions in Mycobacterium tuberculosis 71 and identify crucial errors in ontologies 72 .…”
Section: Figurementioning
confidence: 99%
“…Recent research has shown that AMT and other crowdsourcing platforms can be used to generate corpora for clinical natural language processing and disease mention annotation [41,42]. AMT was used to detect errors in a medical ontology, and it was found that the crowd was as effective as the domain experts [43]. In addition, AMT workers were engaged in identifying disease mentions in PubMed abstracts [42] and rank adverse drug reactions in order of severity [44] with good results.…”
Section: Methodsmentioning
confidence: 99%
“…These are large scale medical taxonomies which have been exploited in modern clinical systems showing significant good results in the targeted clinical systems. In Mortensen et al (2014) it shows that the clinicians using healthcare systems equipped with SNOMED outperformed clinicians using conventional systems without SNOMED CT capabilities.…”
Section: Ontology Driven Clinical Decision Support Frameworkmentioning
confidence: 98%